Review on biohydrogen production by dark fermentative bacteria using starch-containing waste as a substrate - Ulhiza, Tami Asti; Mohamad Puad, Noor Illi; Azmi, Azlin Suhaida (Penerbit Akademia Baru, 2017)
The need of energy has become a global issue that is challenging to the humanity due to its high demand, with fossil fuel is still being the main source of energy. However, fossil fuel is a non-renewable form of energy. The insufficiency of oil reservoir to fulfil overwhelming demands of energy will lead to the energy scarcity. Biohydrogen produced from waste has a potential to be an alternative energy for the future. Numerous papers have discussed biohydrogen process technology using several methods such as dark fermentation, photofermentation and integration of both methods. Unfortunately, there is still lack of papers addressing specifically on what is the most suitable bacteria for biohydrogen production. Dark fermentative bacteria are bacteria that need no light during fermentation. They are reported to be robust and have capability in consuming sludge and waste to synthesize biohydrogen. Therefore, this paper aims to discuss the correlation between dark fermentative bacteria as an agent, with hydrogen yield. The scope of this paper will focus on the performance and requirement of different species of dark fermentative bacteria using starchy waste as substrate.